Is Grand Multiparity Still An Obstetrics Risk? - Ali Abdullah Abbass; Sawsan Talib Salman; Majid Khalil Ali (Diyala Journal of Medicine, 2019)
Background: Grand multiparity has been known to be an obstetric risk because of the documented complications associated with the condition, and it is an indication for booking in a tertiary health institution.